BIOLOGICAL ACTIVITIES OF LONG TERM TREATMENTS WITH HALOXYLON SALICORNICUM AND GLIBENCLAMIDE IN NORMAL AND ALLOXAN HYPERGLYCEMIC DIABETIC RABBITS - AL-Saeed; M.H (Basrah Journal of Veterinary Research)
Hypoglycemic activity of Haloxylon salicornicum and Glibenclamide were studied in normal and diabetic rabbits. The drugs were adminstered once daily at dose of lg / Kg at H.salicorm'cum and 10 mg / Kg at Glibenclamide by gavage for one month. Serum glucose level, creatinine level, total bilirubine and total protein were reduced significantly in 15-30 days. The serum Transaminase (AST and ALT activities) had effect on the treated groups.